Concrete beams reinforced with carbon laminates strips bonded into slits - Barros, Joaquim A. O. (2002)
A strengthening technique based on carbon laminate (CFRP) strips applied into slits cut on the concrete cover, and bonded to concrete by epoxy adhesive, was used for increasing the load bearing capacity of concrete beams failed by bending. This technique avoids the occurrence of the peeling phenomenon, mobilizes high percentage of the full strengthening capacity of the CFRP used, and provides higher protection against fire and vandalism. The adopted strengthening technique is briefly described and the main results obtained are presented and discussed. Using a numerical model developed for non-linear analysis of reinforced concrete structures, the response of the beams tested was predicted. The applicability of this kind of models in such type of reinforced concrete structures is commented.